2012
DOI: 10.2460/ajvr.73.7.1100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term glucose homeostasis in lean and obese cats by use of continuous glucose monitoring

Abstract: Glucose homeostasis was maintained, even in long-term obese cats, and intraday glucose fluctuations were small. One obese cat might have been classified as prediabetic on the basis of the AUCG, which was approximately 25% higher than that of the other obese and lean cats. The CGMS can be useful in the evaluation of long-term effects of drugs or diet on glucose homeostasis in cats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…The feeding method (eg, single meal daily vs multiple meals or continuous access to food) also alters the glucose response with higher glucose peaks after a single large meal. 23,28,29 Furthermore, there is currently no evidence that the reported elevations in blood glucose or insulin are detrimental rather than simply physiologic. Published research also does not support a risk for obesity from carbohydrates in cat foods.…”
Section: Body Weight and Body Composition Changes With Agementioning
confidence: 95%
“…The feeding method (eg, single meal daily vs multiple meals or continuous access to food) also alters the glucose response with higher glucose peaks after a single large meal. 23,28,29 Furthermore, there is currently no evidence that the reported elevations in blood glucose or insulin are detrimental rather than simply physiologic. Published research also does not support a risk for obesity from carbohydrates in cat foods.…”
Section: Body Weight and Body Composition Changes With Agementioning
confidence: 95%
“…Insulin and glucose concentrations were not different in the postprandial state compared with the fasted state in all groups. We have recently shown that obese cats, unless prediabetic, do not have different glucose concentrations than lean cats and do not show great inter-day variability when monitored for a 7-day period during their daily routine with a continuous glucose monitoring system (27). Even when 40% of the diet consisted of glucose, only a small increase in blood glucose was seen at 1 h postfeeding but not at 3 or 6 h (39).…”
Section: Discussionmentioning
confidence: 99%
“…Although most obese cats seem to compensate for their peripheral insulin resistance and maintain normal fasting and post prandial glucose levels for extended periods (Hoenig et al, 2012), obesity in cats is a major risk factor for the development of diabetes. In fact, obese cats have an almost 4 times increased risk of developing diabetes mellitus compared to cats with an optimal body weight (Scarlett and Donoghue, 1998).…”
Section: Dogs and Catsmentioning
confidence: 99%